Steering a path to cultural change: Emerging and enduring characteristics of policing cultures in the UK - Charman, Sarah (International journal of police science & management, 2024)
In the 25 years since the first issue of the International Journal of Police Science & Management was published, policing has undergone significant change as a result of economic, political and social change. Yet this period has unfortunately been bookended by the Macpherson Report in 1999 and the Casey Review in 2023, both highly critical of the occupational cultures within policing. This article takes the issue of policing cultures and examines the extent to which early ethnographic writings on the everyday realities of policing reflect the cultures of today and examines the potential and the desire for both continued research in this area and for cultural change itself. An understanding of cultural characteristics as individual layers contributing to the overall sedimentation of policing practices enables us to see how change, albeit slowly, can potentially happen. The article also suggests, however, that the tendency towards conformity within policing – in terms of both conforming to organisational working practices and norms and conforming to informal occupational cultures – puts pressure on everyone within the policing organisation to ‘fit in’, restricting difference, challenge and ultimately, significant change. A better understanding of the deep roots of occupational cultures within policing and an appreciation of both its benefits and appeal is necessary for a whole organisation approach to reform.